Ação supervisora na educação básica: um estudo sobre o lugar do supervisor escolar nos processos formativos da rede municipal de ensino da cidade de São Paulo - Salmaso, José Luís (2011)
This research had as study object the role of the school supervisor in the municipal educational system of the City of São Paulo. Its objective was to understand the place this professional occupies in this system. The reason for its doing relates to the need of understanding why the school supervisor, in spite of being one of the most experienced professionals in the municipal system and, usually, with the best academic backgrounds, is frequently put aside of the formulation of educational procedures which are established in this system. For the execution of this research, I chose a qualitative approach, and as data gathering procedure, the documental and bibliographical analysis done through means of legislation and the norms which organize the structure and behavior of the studied system and of the revision of literature about the notions of supervision, school supervision, knowledge, formative procedures, educational system, among others. Thereunto I resorted to several authors, amongst which I highlight Saviani (2006), Cortela (2000), Alarcão (2003) and Pineau (2010). The data gathered through bibliographical analysis was completed by the reflexing on the practice itself and through semistructured interviews with educators who acted or act as supervisors in the aforementioned system. The research points out supervisors have occupied different places in the formative procedures which are developed in the municipal system of education. This place had relied on the supervisor personal affinity with the current administration. Such condition allows us to conclude that, in the studied system, the developed policies have been more of floating government policies than permanent estate policies.